Exacerbation of Chronic Obstructive Pulmonary Disease during Outbreak Pandemic - Ulfa Rohmah; Nia Rosliany; Ni Made Suarti (Palembang MediRose Publisher, 2022)
Chronic obstructive pulmonary disease (COPD) during a pandemic is of particular concern because it can worsen the disease. The COVID-19 pandemic is known to cause many deaths and a high spread of the virus. This is a concern for people with COPD regarding the risk of death. The indicator of worsening COPD symptoms is when patients with COPD need to be hospitalized. During the pandemic outbreak, social distancing, use of face masks, and lockdown were implemented. Several studies have reported reduced hospital admissions for COPD exacerbations. It is necessary to intervene judiciously to solve the problem in order to maintain the stability of COPD patients.